2020
DOI: 10.1101/2020.09.27.20202515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of BRCA mutation status on tumor infiltrating lymphocytes (TILs), response to treatment, and prognosis in breast cancer patients treated with neoadjuvant chemotherapy

Abstract: Introduction: Five to 10% of breast cancers (BCs) occur in a genetic predisposition context (mainly BRCA pathogenic variant). Nevertheless, little is known about immune tumor infiltration, response to neoadjuvant chemotherapy (NAC), pathologic complete response (pCR) and adverse events according to BRCA status. Material and methods: Out of 1199 invasive BC patients treated with NAC between 2002 and 2012, we identified 267 patients tested for a germline BRCA pathogenic variant. We evaluated pre-NAC and post-NA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…With the widespread routine use of NAC for TNBC and HER2 -positive BC patients 1 2 , second-line trials in the post neoadjuvant setting for high risk patients are increasing testing the addition of chemotherapy, PARP inhibitors [ 36 ], immunotherapy [ 37 ], cyclin-dependent kinase inhibitors [ 38 ], or vaccines [ 39 ]. We previously demonstrated that TILs-enriched luminal BRCA tumors [ 40 ] and TILs-enriched HER-positive BC tumors are at a high risk of relapse [ 41 ] and could benefit from additional therapies. In the light of these current scientific developments, residual axillary disease is not a predictive factor of the efficacy of such specific therapies, but our findings are of particular importance since they may help to identify more accurately the high-risk patients who might benefit from such treatments by considering the number of residual positive nodes after NAC as a cornerstone of prognostication, provided that it is interpreted according to histological BC subtype.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread routine use of NAC for TNBC and HER2 -positive BC patients 1 2 , second-line trials in the post neoadjuvant setting for high risk patients are increasing testing the addition of chemotherapy, PARP inhibitors [ 36 ], immunotherapy [ 37 ], cyclin-dependent kinase inhibitors [ 38 ], or vaccines [ 39 ]. We previously demonstrated that TILs-enriched luminal BRCA tumors [ 40 ] and TILs-enriched HER-positive BC tumors are at a high risk of relapse [ 41 ] and could benefit from additional therapies. In the light of these current scientific developments, residual axillary disease is not a predictive factor of the efficacy of such specific therapies, but our findings are of particular importance since they may help to identify more accurately the high-risk patients who might benefit from such treatments by considering the number of residual positive nodes after NAC as a cornerstone of prognostication, provided that it is interpreted according to histological BC subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional chemotherapy and radiation treatments have been shown to alter the immune system in head and neck cancer, and TILs have been shown to be predictive of response to neoadjuvant therapy in other tumor types, such as breast cancer. 20-22 Given the evidence of immunomodulatory effects of chemotherapy, we hypothesized that TILs may serve as a predictive biomarker for patients who would ultimately respond to induction chemotherapy. We therefore wished to investigate the role of TILs in predicting response to induction chemotherapy and OS in a cohort of patients undergoing chemotherapy bioselection at our institution.…”
Section: Discussionmentioning
confidence: 99%